Optimized Protocol for Linear RNA Amplification and Application to Gene Expression Profiling of Human Renal Biopsies - A. Scherer; A. Krause; J.R. Walker; S.E. Sutton; D. Serón; F. Raulf; M.P. Cooke (BioTechniques)
Gene expression analysis using high-density cDNA or oligonucleotide arrays is a rapidly emerging tool for transcriptomics, the analysis of the transcriptional state of a cell or organ. One of the limitations of current methodologies is the requirement of a relatively large amount of total or polyadenylated RNA as starting material. Standard array hybridization protocols require 5–15 μg labeled RNA. To obtain these quantities from small amounts of starting RNA material, RNA can be amplified in a linear fashion. Here we introduce an optimized protocol for rapid and easy-to-use amplification of as little as 1 ng total RNA. Our analysis shows that this method is linear and highly reproducible and that it preserves similarities as well as dissimilarities between normal and disease-related samples. We applied this technique to the RNA expression profiling of human renal allograft biopsies with normal histology and compared them to the profiles of renal biopsies with histological evidence of chronic transplant nephropathy or chronic rejection. Among others, complement component C1r was found to be significantly up-regulated in chronic rejection and chronic transplant nephropathy biopsies compared to normal samples, while fructose-1,6-biphosphatase showed lower-than-normal expression.